Bus rapid transit system introduction in Johor Bahru: A simulation-based assessment - Hassan, Sitti Asmah (MDPI AG, 2021)
Bus rapid transit (BRT) is one of the strategies to promote improvements in urban mobil-ity. In this study, BRT scenarios, which integrate exclusive bus lanes and bus priority signal control in mixed traffic scenarios, were modelled using a VISSIM microsimulation. Three scenarios of BRT were modelled to represent 16:84, 38:62 and 54:46 modal splits between public transport and private vehicles. It was found that Scenario 4 (the 54:46 scenario) offers better benefits in terms of delay time saving and economic benefits. In general, it was found that the BRT system enhances the functioning of the transport system and provides people with faster and better mobility facilities, resulting in attractive social and economic benefits, especially on a higher modal split of public transport. It is regarded as one strategy to alleviate traffic congestion and reduce dependency on private vehicles. The finding of this study provides an insight on the effective concept of the BRT system, which may promote the dissemination of an urban mobility solution in the city. The results can help policy-makers and local authorities in the management of a transport network in order to ensure reliable and sustainable transport.